Investigation of ovarian aging markers and hormonal regulation in menopausal transition: Ovarian aging and menopause markers - Samah Amer Hammood; Noor Alamer; Mohammed Kareem S. ALquraish; Majeed, Mohauman M. (Cellular and Molecular Biology, 2025)
Menopause and ovarian dysfunction are consequences of ovarian aging, a continuous and natural process in women. Early symptoms of ovarian aging include inadequate response to ovarian stimulation, irregular menstruation, and loss of follicular function, which collectively contribute to a decline in fertility as women age. The effects of aging on the ovaries are more pronounced than on other organs, with deterioration in the follicular pool and oocyte quality influenced by endocrine, genetic, and metabolic factors. This study aimed to examine the correlation between menopausal symptoms and serum levels of vitamin D, anti-Müllerian hormone (AMH), and other fertility-related hormones, as well as their impact on the timing of menopause. Ninety-two female participants were recruited from the Fertility Center Laboratories and AL-Saader Medical City in Al-Najaf province. A structured questionnaire assessing age, weight, height, and the severity of eleven menopausal symptoms—rated on a scale from 0 (absent) to 4 (extremely severe)—was administered. Symptoms evaluated included hot flushes, heart discomfort, sleep disturbances, muscle and joint pain, psychological issues, and urogenital problems. Serum levels of follicle-stimulating hormone (FSH), 25-hydroxyvitamin D, AMH, and luteinizing hormone (LH) were measured using the ELISA method. The results showed a significant negative correlation between serum AMH and vitamin D levels with menopausal symptoms and advancing age in postmenopausal women. Vitamin D levels were also negatively correlated with age, depression scores, and body mass index (BMI). Women with vitamin D deficiency and decreased AMH experienced more severe menopausal symptoms such as hot flushes, heart discomfort, depression, irritability, bladder problems, and musculoskeletal pain. These findings suggest that low AMH and vitamin D levels during menopause, compared to younger control women aged 20–40 years, may exacerbate menopausal symptoms. Supplementation with vitamin D, AMH, and reproductive hormone regulators, alongside lifestyle management, may benefit menopausal women suffering from fertility decline and severe menopausal symptoms.